Converging Nanochemistry: From Disease Prevention to Diagnosis and Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue covers recent research in nanochemistry convergence from disease prevention to diagnosis and treatment. It includes studies on new (bio)molecules and hybrids with diagnostic, chemopreventive, or therapeutical properties; novel nanobioengineered biosensors for disease diagnostics; and nanoparticles and nanobioconjugates for targeted drug delivery. The Special Issue collects a benchmark of state-of-the-art works on the computational simulation, structural modeling, and construction of new libraries of molecules to identify potential targets, synthesize molecules, and study their potential in developing diagnostic and therapeutic tools. It illustrates other topics that go from directed evolution techniques to help create mutants of proteins with enhanced activity concerning the native structures to reviews on nanobioprobes using conjugation approaches and biosensors as promising tools for disease detection. The Special Issue also provides examples of drug delivery systems based on biocompatible and biodegradable materials for chemoprevention.